Al di là del diritto. Il “passo” di Jacques Derrida - Andronico, Alberto (Bollettino Filosofico, 2021)
The thesis of this essay is that a jurist should read Derrida because deconstruction allows to take a step beyond the theory of law that still today believes that it must leave aside issues such justice or power, thus repeating obsessively that law is nothing but law founded on law. What is at stake, however, is a step beyond the law (and its theory) which is also a step beyond, pointing towards a different origin. Keywords: Deconstruction, Democracy, Force, Justice, Law